Trifluoromethylthiolation and Trifluoromethylselenolation of α‐Diazo Esters Catalyzed by Copper. Issue 35 (28th July 2016) - Matheis, Christian; Krause, Thilo; Bragoni, Valentina; Goossen, Lukas J.
Abstract: α‐Diazo esters are smoothly converted into the corresponding trifluoromethyl thio‐ or selenoethers by reaction with Me4 NSCF3 or Me4 NSeCF3, respectively, in the presence of catalytic amounts of copper thiocyanate. This straightforward method gives high yields under neutral conditions at room temperature and is applicable to a wide range of functionalized molecules, including diverse α‐amino acid derivatives. It is well‐suited for the late‐stage introduction of trifluoromethylthio or ‐seleno groups into drug‐like molecules. Abstract : Simple and effective : In the presence of catalytic amounts of copper thiocyanate, α‐diazo esters are smoothly converted into the corresponding trifluoromethyl thio‐ or selenoethers by reaction with inexpensive, easy‐to‐store and handle Me4 NSCF3 or Me4 NSeCF3, respectively. This straightforward method gives high yields under neutral conditions at room temperature and is applicable to a wide range of functionalized molecules.